MRI Patterns of brain injury and neurodevelopmental outcomes in neonates with severe anaemia at birth. (February 2017) - Loureiro, Begoña; Martinez-Biarge, Miriam; Foti, Francesca; Papadaki, Maria; Cowan, Frances M; Wusthoff, Courtney J
Abstract: Aims: To define patterns of brain injury and associated neurodevelopmental outcomes in infants with severe neonatal anaemia. Methods: We studied 20 infants with severe anaemia at birth (haemoglobin < 7 g/dL). Clinical details were analysed for causes of anaemia and co-morbidities. All had early brain magnetic resonance imaging (MRI) scans, which were reviewed for injury pattern. Neurodevelopmental outcomes were assessed at a median age of 24 months. Results: The aetiology of the anaemia was feto-maternal haemorrhage in 17 and antepartum haemorrhage in 3 infants. The predominant site of injury was the white matter, which was affected in all infants, with differing grades of severity and with cystic evolution in 45%. Only one infant showed an injury pattern typical of an acute severe hypoxic-ischaemic insult. Outcomes correlated closely to the severity of MRI findings. Cerebral palsy was seen only with the most severe neuroimaging patterns (n = 6). Global developmental delay, learning or behavioural problems and seizures were common with moderate injury. Visual impairment occurred, particularly with posterior injury. Microcephaly developed in 45%. Interpretation: Severe neonatal anaemia at birth was associated with a white matter predominant pattern of injury, the severity of which was related to neurodevelopmental outcomes. Early MRI and long-term follow-up are advisable following severe neonatal anaemia. Highlights: White matter injury is the imaging signature associated with severe neonatal anaemia. Additional basal ganglia-thalamic injury can be seen in the severest cases. Developmental outcomes correlated well with injury severity assessed from early MRI. Neonatal MRI and long-term follow-up are advisable in infants with severe anaemia at birth.